2021
DOI: 10.3389/fpsyg.2021.648405
|View full text |Cite
|
Sign up to set email alerts
|

Different Populations Agree on Which Moral Arguments Underlie Which Opinions

Abstract: People often justify their moral opinions by referring to larger moral concerns (e. g., “It is unfair if homosexuals are not allowed to marry!” vs. “Letting homosexuals marry is against our traditions!”). Is there a general agreement about what concerns apply to different moral opinions? We used surveys in the United States and the United Kingdom to measure the perceived applicability of eight concerns (harm, violence, fairness, liberty, authority, ingroup, purity, and governmental overreach) to a wide range o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…The method we use for measuring the argument advantage of a moral opinion has been described in detail in prior work [ 5 , 11 ]. It relies on a list of generic moral arguments derived from moral foundations research [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The method we use for measuring the argument advantage of a moral opinion has been described in detail in prior work [ 5 , 11 ]. It relies on a list of generic moral arguments derived from moral foundations research [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Using this procedure, the argument advantage of 98 moral opinions covered by the General Social Survey (GSS) [ 17 ] was estimated by Vartanova and colleagues [ 11 ]. Importantly, even though the argument advantage measure of an opinion is a subjective measure aggregated across many respondents, it was found to be robust across demographic groups.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…On any given issue, one opinion will therefore have a "HVFL argument advantage" in the sense that this opinion is easier to justify by the generally acceptable HVFL kinds of arguments than the opposite opinion is. Studies conducted in the United States, the United Kingdom, Brazil, and Israel have demonstrated that measures of which arguments justify which opinions are virtually identical across different groups, such as across liberals and conservatives (Vartanova et al, 2021). Thus, these measures reflect genuine connections between opinions and different kinds of arguments, the perceptions of which are largely independent of what opinion people hold (Strimling et al, 2019).…”
Section: The Moral Argument Theory Of Opinion Dynamicsmentioning
confidence: 99%
“…From the General Social Survey items included in any of the six aforementioned waves, we selected 81 items previously identified as opinions on moral issues (Vartanova et al, 2021). A full list is provided in Supplementary Table 2.…”
Section: Moral Opinionsmentioning
confidence: 99%